2018
DOI: 10.1642/auk-18-23.1
|View full text |Cite
|
Sign up to set email alerts
|

Where do winter crows go? Characterizing partial migration of American Crows with satellite telemetry, stable isotopes, and molecular markers

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…We also determined that strategy was not fixed: 5 of the 23 birds captured in multiple years changed strategies between winters. While studies of some partially migratory systems have found strategy switching to be uncommon (Gillis et al , Townsend et al ), our results are consistent with the larger number of studies that have found individual strategies are flexible (Able and Belthoff , Ogonowski and Conway , Palacín et al , Hegemann et al ). The occurrence of strategy switching in western bluebirds suggests that migratory strategy is not controlled by a simple genetic dimorphism in this system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also determined that strategy was not fixed: 5 of the 23 birds captured in multiple years changed strategies between winters. While studies of some partially migratory systems have found strategy switching to be uncommon (Gillis et al , Townsend et al ), our results are consistent with the larger number of studies that have found individual strategies are flexible (Able and Belthoff , Ogonowski and Conway , Palacín et al , Hegemann et al ). The occurrence of strategy switching in western bluebirds suggests that migratory strategy is not controlled by a simple genetic dimorphism in this system.…”
Section: Discussionsupporting
confidence: 90%
“…Chan () found that some birds only developed migratory restlessness in the presence of others, an observation which led him to suggest interactions with other individuals may be a key cue for initiating migration in this species (Chan and Kikkawa , Chan ). Social influences have been proposed to play a role in determining migratory strategies in other species, such as great bustards Otis tarda (Palacín et al ), and pied avocets Recurvirostra avosetta (Chambon et al ), where strategies appear to be influenced by an individual's integration into winter flocks.…”
Section: Introductionmentioning
confidence: 99%
“…The potential costs of migration are high: migratory individuals may encounter unfamiliar environments with novel threats, as well as the energetic costs of movement (Wikelski et al, ), predation risks (Lindström, ; Ydenberg, Butler, Lank, Smith, & Ireland, ) and temporal investment to the detriment of time otherwise invested in breeding fitness (Alerstam et al, ). The biological processes underlying the evolution of migration are little known (Griswold, Taylor, & Norris, ; Townsend, Frett, McGarvey, & Taff, ; Vélez‐Espino, McLaughlin, & Robillard, ), but in order to have evolved, migration must—in sufficient instances—offer a benefit relative to not migrating (‘residency’ hereafter) to either breeding success or survival (Griswold et al, ; Lundberg, ; McKinnon et al, ; Zúñiga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we included as “potential breeders” all adult birds sampled during the breeding season (June through August) in each of the two study populations within the same 4‐km‐diameter areas from which we sampled nestlings (Figure ; California: n = 258 males, 134 females, and 262 offspring; New York: n = 33 males, 38 females, and 134 offspring). Individuals at this scale interacted with each other in the winter months at communal roosts and local diurnal activity centres, as indicated by satellite telemetry, GPS telemetry and mark–resight data (Taff et al., ; Townsend, Frett, McGarvey, & Taff, A.K. Townsend, unpublished data).…”
Section: Methodsmentioning
confidence: 88%